The Iraq effect : the Middle East after the Iraq War - Wehrey, Frederic M.; Rand Corporation; Project Air Force (U.S.) (Santa Monica, CA : RAND, 2010)
The conflict in Iraq has reverberated across the Middle East, affecting the balance of power between neighboring states, their internal political dynamics, how their publics view American credibility, and the strategies and tactics of al-Qa'ida. No matter how the internal situation in Iraq evolves, its effects on the broader region will be felt for decades, presenting new challenges and opportunities for U.S. policy. A better understanding of how regional states and nonstate actors have responded to the Iraq conflict will better prepare the United States to manage the war's long-term consequences. To that end, the authors conducted extensive fieldwork in the region and canvassed local media sources to inform their analysis. Among their key findings: The war has facilitated the rise of Iranian power in the region, but Iran faces more limits than is commonly acknowledged; the war has eroded local confidence in U.S. credibility and created new opportunities for Chinese and Russian involvement; the war has entrenched and strengthened neighboring Arab regimes while diminishing the momentum for political reform; and the war has eroded al-Qa'ida's standing in the region, but the network and its affiliates are adapting with new tactics and strategies.
Introduction -- An altered strategic landscape : the shifting regional balance of power -- New challenges to American influence : Chinese and Russian roles in the Middle East -- Domestic reverberations of the war : internal challenges to regime stability -- The Iraq War and the future of terrorism : lessons learned and new strategic trends -- Conclusion : managing the aftershocks of Iraq and seizing opportunities.
"Prepared for the United States Air Force."
Includes bibliographical references (pages 159-187).
Print version record.
eBooks on EBSCOhost
Keywords: Iraq War, 2003-2011 -- Influence; United States -- Foreign relations -- Middle East; Middle East -- Foreign relations -- United States; Middle East -- Strategic aspects; Guerre en Irak, 2003-2011 -- Influence; États-Unis -- Relations extérieures -- Moyen-Orient.; Moyen-Orient -- Relations extérieures -- États-Unis.; HISTORY -- Military; HISTORY -- Asia -- Central Asia; Diplomatic relations; Influence (Literary, artistic, etc.); Strategic aspects of individual places; Iraq; Middle East; United States; Irakkriget 2003- -- influenser; Middle East -- regional development; 2003-2011